2008
DOI: 10.1177/1049731508329395
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and Correlates of Client Satisfaction

Abstract: Client satisfaction surveys give clients a voice in the planning and management of services. While their use is quite widespread, they have hardly at all been used in the evaluation of shelters for homeless youths. In this article, the authors present findings of a client satisfaction survey conducted among residents of a shelter for homeless youths in Tel Aviv, Israel, shortly after their departure from the shelter. Satisfaction was affected mainly by three aspects of life in the shelter—the staff, the food, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…These three items were used to check the concurrent validity of the SOES for two reasons. First, domain-specific subjective evaluations (e.g., perceptions on program quality and instructor performance) are generally regarded as conceptually related yet distinct constructs from global satisfaction (e.g., overall satisfaction with the project; Spiro et al, 2009). Second, according to the current conceptual framework of subjective outcome evaluation (Shek & Ma, 2014) and previous findings (Shek & Law, 2014;Shek, Yang, et al, 2020), participants' perceptions of the three aspects included in the SOES are key determinants of their willingness to recommend the project and participate in similar projects and overall satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…These three items were used to check the concurrent validity of the SOES for two reasons. First, domain-specific subjective evaluations (e.g., perceptions on program quality and instructor performance) are generally regarded as conceptually related yet distinct constructs from global satisfaction (e.g., overall satisfaction with the project; Spiro et al, 2009). Second, according to the current conceptual framework of subjective outcome evaluation (Shek & Ma, 2014) and previous findings (Shek & Law, 2014;Shek, Yang, et al, 2020), participants' perceptions of the three aspects included in the SOES are key determinants of their willingness to recommend the project and participate in similar projects and overall satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the societal and academic interest in dealing with the problem of homelessness (Lorber, 2009) and intimate partner violence (Waltermaurer, 2006), there are very few studies on how clients themselves experience the services they receive (Spiro, Dekel, & Peled, 2009;Wolf, Luijtelaar, Jansen, & Altena, 2007). The few studies on client satisfaction among homeless people and youth were mostly conducted in the United States, with instruments that were often not specifically designed for or tailored to the target population (Calsyn, Morse, Klinkenberg, Yonker, & Trusty, 2002;Kasprow, Frisman, & Rosenheck, 1999;Klinkenberg, Calsyn, & Morse, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, no relationship between client satisfaction and the behavioral outcome of compliance with child support orders was observed. Finally, in a study of a shelter for homeless youth in Israel, satisfaction reported by 102 residents was related to their adaptation to the program but was unrelated to their reasons for leaving the shelter (Spiro, Dekel, & Peled, 2009). On balance, the findings are mixed and seem to support Weinbach's (2005, p. 38) warning, '' .…”
Section: Satisfaction As An Indicator Of Service Outcomes: Concurrent Validitymentioning
confidence: 88%
“…Some studies reported two kinds of validity analyses. For example, Spiro, Dekel, and Peled, (2009) assessed content validity (i.e., the degree to which items appear to reflect the content of a construct) by consulting with program staff and a steering committee, and they used correlations with other outcomes as an indicator of concurrent validity. Four studies reported validity analyses, but methods were not described.…”
Section: Validity and Reliability Of Consumer Satisfaction Measuresmentioning
confidence: 99%